1999
DOI: 10.1038/sj.bjc.6690353
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tissue-type plasminogen activator (tPA) and its complex with the type-1 inhibitor (PAI-1) in breast cancer

Abstract: SummaryThe prognostic value of tissue-type plasminogen activator (tPA) measured in samples derived from 865 patients with primary breast cancer using a recently developed enzyme-linked immunosorbent assay (ELISA) was evaluated. Since the assay could easily be adapted to the assessment of the complex of tPA with its type-1 inhibitor (PAI-1), it was investigated whether the tPA:PAI-1 complex also provides prognostic information. To this end, cytosolic extracts and corresponding detergent extracts of 100 000 g pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
7
27
1
Order By: Relevance
“…PAI-1 is thought to inhibit activation of tPA or uPA, an event that correlates with poor clinical outcomes in cancer (45,46); however, PAI-1 also serves as an indicator of poor prognosis in breast cancer (47). These findings may be attributed to differences in cell types and experimental models.…”
Section: Discussioncontrasting
confidence: 42%
“…PAI-1 is thought to inhibit activation of tPA or uPA, an event that correlates with poor clinical outcomes in cancer (45,46); however, PAI-1 also serves as an indicator of poor prognosis in breast cancer (47). These findings may be attributed to differences in cell types and experimental models.…”
Section: Discussioncontrasting
confidence: 42%
“…Evidently, this finding is a (de Witte et al, 1999a), and for tPA, 2.40 and 13.01 ng mg protein -1 (de Witte et al, 1999b). These biochemical assays are very sensitive and easily can be performed on as little as 25 mg of tissue.…”
Section: Discussionmentioning
confidence: 81%
“…The complex selectively reflects the amount of uPA that has been activated from proenzyme uPA and subsequently inactivated by PAI-1. We have earlier shown that the complex of tissue-type plasminogen activator:PAI-1 as measured in the soluble, nonmembrane bound fraction has significant clinical relevance in terms of RFS and OS, whereas levels in pelleted (membrane) fractions were substantially less relevant (17). Furthermore, the levels of uPA and PAI-1 in the pellet extracts provided less prognostic information as compared with those in the soluble, nonmembrane bound extracts (30).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it can be hypothesized that the tumor levels of uPA:PAI-1 complex may provide valuable predictive information in patients with primary breast cancer. In the current study we focused on the clinical relevance of the complex in the soluble, nonmembrane bound fraction, because in an earlier study it was shown that the complex of tissue-type plasminogen activator:PAI-1 as measured in the soluble fraction has clinical relevance in terms of relapse-free survival (RFS) and overall survival (OS), whereas levels in pelleted (membrane) fractions were substantially less relevant (17).…”
Section: Introductionmentioning
confidence: 99%